Software durability concepts and practices - Kumar, Rajeev 1991-; Khan, Suhel Ahmad; Khan, R. A. (CRC Press, 2023)
Software evolution is a time-consuming and costly process due to its complex architecture. Software designers need to produce software that is effective as well as durable. Durability and effectiveness of software are the foremost priorities and challenges for developers. This book comprises real-life case studies of durability issues and their solutions that bring to light loopholes and show how to fix them, to enhance durability. Existing literature on software durability tells us that the first step is to recognise the problem. It gives information about durability, risk, estimation, knowledge, and governance based on five main characteristics: dependability, trustworthiness, usability, security, and human trust. The book serves as a complete package to get acquainted with assurance and risk management from a software durability perspective. It enhances our understanding of the concept of durability, its multi-dimensional approach, threats and their types, risk, mitigation techniques, and suggestive measures. The book reviews the emerging trends in the software development process in the context of durability concepts such as automated code reviews, coding standards, and software durability standards and their testing, cost management solutions, low-code or no-code solutions, and durability assurance.